Chemical and Technological Characterization of Dairy Products - Faccia, Michele (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Milk processing is one of the most ancient food technologies, dating back to around 6000 B.C. A huge number of milk products have been developed worldwide, representing a spectacular example of biodiversity and a priceless cultural heritage. After millennia of unanimous appreciation as a pillar of human nutrition, a series of questions about the desirability of their wide consumption have been raised. In the light of the growing threat deriving mostly from the spread of veganism and health consciousness, improving milk prcoessing safety and dairy nutritional characteristics, as well as deepening their functional characteristics, are of a primary exigency. This Special Issue contains several articles focusing on this hot topic, all of which add knowledge to the field and supply interesting ideas for developing new products and processes.